Le cirque de Lugdunum : données anciennes et récentes - Michèle Monin; Djamila Fellague (Gallia)
Due to recent discoveries, we propose a new approach of the location of the circus at Lugdunum. A new reading of earlier documentation, an overview of the various hypotheses, the study of epigraphic and stone testimonies, and a topographical analysis allow a series of arguments for a location of the circus on the plateau of Fourvière, westwards from the street Pauline-Marie-Jaricot (5th district). This monument could extend north up to the modern fortifications and south, adjacent to the aqueduct of Gier. The masonry substructions uncovered underneath the street Henry-Le Chatelier may correspond to the west wing of the cavea and are figured by a range of four cells and the initial section of a fifth one, designed to support the seating tiers. By their measurements and mode of construction, they remind of modules, which are characteristic of circus architecture in Antiquity. The topographical survey of the area also confirms the technical possibility of a circus being sited on this spot. Finally, formerly non-interpreted findings may belong to the remains of the east front of the building.